Occurrence of adverse events associated with the initiation of methotrexate and biologics for the treatment of psoriasis in routine clinical practice - Faizan Mazhar; Åsa Krantz; Lovisa Schalin; Josefin Lysell; Juan Jesus Carrero (Taylor & Francis Group, 2023)
Background: Limited information exists on the risk of adverse events (AEs) attributed to methotrexate (MTX) and biologics for the treatment of psoriasis/psoriatic arthritis (PsA/PsO) in heterogeneous clinical practice and beyond the duration of clinical trials. Methods: An observational study of 6294 adults with incident PsA/PsO who initiated MTX or biologics in Stockholm from 2006-2021 was conducted. The risk of kidney, liver, hematological, serious infectious, and major gastrointestinal AEs was quantified and compared between therapies using incidence rates, absolute risks, and adjusted hazard ratios (HRs) from propensity-score weighted Cox regression. Results: Median follow-up was 4.3 (2-7) years. Users of MTX had a higher risk of anemia (HR 1.79 [95% CI, 1.48-2.16]), particularly mild-moderate anemias (1.93;1.49-2.50), and mild (1.46;1.03-2.06) and moderate-severe liver AEs (2.22;1.19-4.15) compared to biologics. Chronic kidney disease incidence did not differ between therapies (affecting 1.5% of the population in 5 years; HR:1.03;0.48-2.22). Acute kidney injury, serious infections, and major gastrointestinal AEs showed low absolute risks and no clinically meaningful differences between both therapies. Conclusion: The use of MTX for psoriasis patients in routine care was associated with a higher risk of anemia and liver AEs than biologics, but similar risks of kidney, serious infections, and major gastrointestinal AEs.